Pengelompokkan Provinsi di Indonesia Berdasarkan Faktor Penyebab Balita Stunting Menggunakan Analisis Cluster Hierarki - Dodi Satriawan; Dwi Agus Styawan (Jurnal Statistika dan Aplikasinya, 2021)
The stunting condition is characterized by the growth of childrens who are slow and fail to reach normal height. Some of the causes of stunting include household access to sanitation and drinking water sources, initiation of early breastfeeding, exclusive breastfeeding, full immunization, household income, and household access to nutritious food. This study aims to classify provinces in Indonesia based on the causes of stunting. The source of the data used is secondary data from the Ministry of Health and BPS in 2017. Clustering was carried out using the ward method cluster analysis. The clustering results are four groups with different characteristics. The first group of 16 provinces was a group with a high stunting factor. The second group consisting of 8 provinces was a group with a moderate stunting factor. The third group consisting of 6 provinces is a group with a low stunting factor. The fourth group consisting of 4 provinces is a group with a very high stunting factor.